Relationship Between Transport Expenditure in Public Investment and Economic Growth in Nepal - K.C., Nurjang (DEPAN, 2024)
Nepal, focusing on the impact of capital and recurrent expenditures on GDP from 1980 to 2023. Using the ARDL bounds testing approach, the analysis confirms a long-run cointegration relationship between GDP and selected variables, such as expenditures on transportation and social sectors. The results indicate that recurrent and capital expenditures have a positive and significant effect on GDP in both the short and long run. The error correction term reveals a rapid adjustment toward equilibrium. Statistical tests confirm the absence of serial correlation and heteroscedasticity, while stability tests validate the robustness of the model. The findings highlight a shift toward a private-sector-led economy post-liberalization and underscore the importance of efficient expenditure management to foster sustainable economic growth. This study provides valuable insights for policymakers to design strategies that optimize public expenditure for long-term development.